Characterization of Mannanase Isolated from Corncob Waste Bacteria - Wahyuni, S.; Khaeruni, A.; Purnomo, A.S.; Asranudin; Holilah; Fatahu (Asian Journal of Chemistry, 2017)
Mannanase bacteria has been isolated from some sources such as oil waste, activated sludge, decayed konjac, soil and sagoo hump, which mannanase enzyme has been isolated from bacteria, fungi and some fruits. This study focused on the characterization of mannanase bacteria isolated from corncobs waste. Nine isolates bacteria were successfully screened, which 2 isolates showed the greatest mannolitic index i.e., IB.1.6 and IB.1.10. The character of both isolates were Gram-negative and rod cells. Characteristics physiology of IB.1.6 and IB.1.10 isolates showed positive result on the fermentation of mannose, rhamnose, lactose and glucose, as well as utilization of citrate and catalase. Mannanase from IB.1.6 and IB.1.10 isolates were stable at wide temperature range 30-90 °C and pH range 5-8, which temperature and pH optimum of 60 and 8 °C, respectively. Type of metal ion (Co2+ and Cu2+) and surfactants (Tween 20 and Tween 80) affected the activity of 2 enzymes.